Formulation and Characterization of Losartan Loaded Chitosan Microspheres: Effect of Crosslinking Agents - Pahuja, Sonia; Aggarwal, Shweta; Sarup, Prerna (Drug Research, 2020)
Objective The present investigation entailed determination of effect of diverse cross-linking agents on Losartan Potassium loaded chitosan microspheres. The emulsion cross-linking method was employed to formulate the microspheres with an endeavour to achieve maximum sustained effect.Methods The FTIR studies revealed absence of any interaction between Losartan and chitosan. The emulsion cross linking method was accomplished in three steps encompassing formation of an aqueous and oily phase, emulsification and cross-linking. A total of eighteen Losartan formulations were developed using six different cross-linkers at three varying level were screened for optimum parameters. The in vitro drug release parameters of optimum formulations (LC3, LE3, LF3, LG3, LS3 and LV3) containing citric acid, epichlorohydrin, formaldehyde, glutaraldehyde, suphuric acid and vanillin as cross-linkers were assessed to determine the sustained effect.Results The values of evaluated parameters including percent yield (94.67%), average particle size (51.19 µm), drug content (44.38 mg) and entrapment efficiency (88.77%) connoted LG3 as the best formulation. Additionally, the values of relative measure of skewness (β1=0.01 and γ1=0.10) and platykurtic (β2=1.26) size distribution were least for LG3 with spherical shape and smooth surface as revealed by SEM studies.Conclusion The outcome of in vitro release and other characterizations of microspheres explicitly revealed glutaraldehyde as the best cross-linker amongst the cross-linkers used herewith. The maximum sustained effect (lasting over a period of 24 h) accompanied with higher MDT and t50% with lower%DE and Q14h values thus corroborated the objective of attaining sustained release of Losartan.
Keywords: losartan potassium; chitosan; cross-linking agents; emulsion cross-linking; sustained drug delivery